PEMBUATAN PERANGKAT PEMBELAJARAN TARI MELAYU BERBASIS HIGH ORDER THINKING SKILLS (HOTS) UNTUK SISWA/I KELAS VIII SMP NEGERI 1 TANJUNG TIRAM - Jefri Jefri; Yusnizar Heniwati (Universitas Negeri Medan, 2020)
ABSTRACTThis research aims to make learning tools for Malay Dance based on High Order Thinking Skills (HOTS) for students of class VIII of SMP Negeri 1 Tanjung Tiram. This study uses theories related to topics such as packaging theory, learning, teaching materials in the form of textbooks and HOTS-based student worksheets. The main theory used in this thesis uses the theory of Andi Prastowo (2014: 17) which states that